Phát triển năng lực dạy học trong môi trường số cho sinh viên Sư phạm Hóa Học dựa trên mô hình TPACK - Vũ , Thị Thu Hoài (Tạp chí Giáo dục, 2025)
In the context of educational digital transformation, digital competence has become an essential requirement for 21st-century teachers. The study proposes a competency framework for teaching in digital environments for pre-service chemistry teachers, which is developed based on the TPACK model. This framework was also implemented as an expected learning outcome. Data were collected through peer assessment and self-assessment of students’ teaching performance based on the proposed framework. The results revealed significant improvements in students’ digital teaching competence after the intervention, highlighting the positive impact of integrating digital tools into teaching practice. These findings underscore the TPACK model as a solid foundation for developing teaching competence in digital environments among pre-service teachers. The study provides practical implications for innovating teacher education programs in the digital transformation era and suggests directions for further research on enhancing teaching competence in technology-integrated learning environments.